Impact of Intravascular Ultrasound–Derived Lesion-Specific Virtual Fractional Flow Reserve Predicts 3-Year Outcomes of Untreated Nonculprit Lesions: The PROSPECT Study. (15th November 2022) - Seike, Fumiyasu; Mintz, Gary S.; Matsumura, Mitsuaki; Ali, Ziad A.; Liu, Mengdan; Jeremias, Allen; Ben-Yehuda, Ori; De Bruyne, Bernard; Serruys, Patrick W.; Yasuda, Kazunori; Stone, Gregg W.; Maehara, Akiko
Abstract : Background: Hemodynamic assessment of untreated nonculprit lesions was not studied in the PROSPECT study (Providing Regional Observations to Study Predictors of Events in the Coronary Tree). We developed a virtual intravascular ultrasound–derived lesion-specific fractional flow reserve (lesion-specific IVUS-FFR) algorithm to assess individual lesion-level FFR. We sought to investigate the relation between lesion-specific IVUS-FFR and major adverse cardiovascular events (MACE) arising from untreated nonculprit lesions in the PROSPECT study. Methods: In PROSPECT, 697 patients with acute coronary syndromes underwent 3-vessel grayscale and virtual histology–IVUS to correlate untreated nonculprit plaque morphology with 3-year nonculprit related MACE (composite of cardiac death, cardiac arrest, myocardial infarction, or rehospitalization due to unstable or progressive angina). Lesion-specific IVUS-FFR was calculated from volumetric IVUS lumen area measurements at 0.4 mm intervals by applying a mathematical circulation model using basic fluid dynamics equations. Results: Lesion-specific IVUS-FFR was analyzable in 3227 nonculprit lesions in 660 patients among whom 54 nonculprit MACE events (3 myocardial infarctions) occurred at median 3.4-year follow-up. By receiver-operating characteristic analysis, the best cutoff value of lesion-specific IVUS-FFR to predict nonculprit MACE was ≤0.95. After adjusting for patient and lesion characteristics, lesion-specific IVUS-FFR (hazard ratio, 4.83 [95% CI, 2.20–10.61]; P <0.001) was an independent predictor of 3-year nonculprit MACE, in addition to minimum lumen area≤4.0 mm 2, plaque burden ≥70%, and virtual histology thin-cap fibroatheroma. Conclusions: Minor reductions in lesion-specific IVUS-FFR were independently associated with future nonculprit MACE arising from untreated angiographically mild stenoses along with previously established high-risk lesion morphological characteristics. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00180466.